Apis mellifera subsp. scutellata Lepeletier 1836 - Platt, Steven G.; Rainwater, Thomas R.; McMurry, Scott T. (Zenodo, 2021)
Honeybees ( Apis mellifera scutellata) A colony of Africanised honeybees was present during July and August 1997 (and perhaps longer) in a hollow stump located approximately 2 m from a C. moreletii nest on a low-lying island in GBL. The bees aggressively defended the area surrounding the nest and one of us (TRR) together with an accompanying dog ( Canis lupus familiaris ) were stung repeatedly as we attempted to remove, measure, and weigh eggs at the nest. The honey bee colony was no longer present when we returned to the island in 1998 or thereafter. : Published as part of Platt, Steven G., Rainwater, Thomas R. & McMurry, Scott T., 2021, Fauna associated with the nests of Crocodylus moreletii and Crocodylus moreletii × acutus in Belize, pp. 133-149 in Journal of Natural History 55 (3 - 4) on page 138, DOI: 10.1080/00222933.2021.1895350, http://zenodo.org/record/5469892